Monotheism and tolerance: recovering a religion of reason - Erlewine, Robert (Indiana series in the philosophy of religion, 2010)
Part I: Overcoming the current crisis -- Monotheism, tolerance, and pluralism : the current impasse -- Learning from the past : introducing the thinkers of the religion of reason -- Part II: Mendelssohn : idolatry and indiscernability -- Mendelssohn and the repudiation of divine tyranny -- Monotheism and the indiscernible other -- Part III: Kant : religious tolerance -- Radical evil and the mire of unsocial sociability -- Kant and the religion of tolerance -- Part IV: Cohen : ethical intolerance -- Cohen and the monotheism of correlation -- Cohen, rational supererogation, and the suffering servant -- Conclusion: Revelation, reason, and the legacy of the Enlightenment